Global potential of interaction for 16O + 12C- and 12C + 12C-diffractive scattering in the wide energy range - O. A. Ponkratenko; A. A. Rudchik; A. T. Rudchik; Yu. M. Stepanenko; V. V. Uleschenko; Yu. O. Shyrma (Ядерна фізика та енергетика)
Detailed study of the behavior of experimental differential cross sections for the 16О + 12С-, 12С + 12С-elastic scatte¬ring in the energy range from 1 to 200 MeV/nucleon have been carried out. It is found that differential cross sections in the range of transfer momentum from 0 to 3-4 fm-1 shows the diffraction character for scattering in the overall energy range. The behavior features of the allocations of the first eight diffraction maxima and minima as well values of cross-sections in the maxima at the change of the interaction energy have been analyzed. It has been received energy-dependent optical potentials of the interaction for examines systems at the full range of energies. The obtained potentials describe the available experimental data satisfactorily and reproduce typical features of diffractive scattering cross sections.